Students' clarification stages in analyzing mathematical problems in the implementation of the OBE curriculum - Moh. Mahfud Effendi; Alfiani Athma Putri Rosyadi (Universitas Muhammadiyah Malang, 2024)
Solving mathematical problems is an important aspect of the learning process, but in reality, many students experience difficulty in solving them. The aim of this research is to explain the stages of student qualifications in analyzing mathematical problems, especially in implementing the OBE curriculum. This qualitative descriptive research uses an interactive model, with a sample size of 40 students taking the Euclidean Geometry course. Data collection uses questionnaires, tests and interviews which have been declared valid with a score of 90% and reliable with a score of 87%. Data collection stages include; (1) differentiating, (2) organizing, and (3) connecting aspects. Students' clarification stages in the analytical process of solving mathematical problems consist of differentiating, organizing and connecting. Analysis of research data uses descriptive, namely percentages. Based on the results of the analysis, it is known that the level of clarity of students in analyzing mathematical problems is 66.67%, and only 20% of students have a level of conformity of 100%. The organizing stage had the lowest score (60%) compared to the differentiating (66.67%) and connecting (73.33%) stages. The advice that can be given is that at the deconstruction stage, it can be studied if there are differences of opinion, while in the exploration process, it can be explained using HOTS.